Interacting Cannabinoid and Opioid Receptors in the Nucleus Accumbens Core Control Adolescent Social Play - Manduca, Antonia; Lassalle, Olivier; Sepers, Marja; Campolongo, Patrizia; Cuomo, Vincenzo; Marsicano, Giovanni; Kieffer, Brigitte; Vanderschuren, Louk J. M. J; Trezza, Viviana; Manzoni, Olivier J. J. (Frontiers in Behavioral Neuroscience, 2016)
Social play behavior is a highly rewarding, developmentally important form of social interaction in young mammals. However, its neurobiological underpinnings remain incompletely understood. Previous work has suggested that opioid and endocannabinoid neurotransmission interact in the modulation of social play. Therefore, we combined behavioral, pharmacological, electrophysiological and genetic approaches to elucidate the role of the endocannabinoid 2-arachidonoylglycerol (2-AG) in social play, and how cannabinoid and opioid neurotransmission interact to control social behavior in adolescent rodents. Systemic administration of the 2-AG hydrolysis inhibitor JZL184 or the opioid receptor agonist morphine increased social play behavior in adolescent rats. These effects were blocked by systemic pretreatment with either CB1 cannabinoid receptor (CB1R) or mu-opioid receptor (MOR) antagonists. The social play-enhancing effects of systemic morphine or JZL184 treatment were also prevented by direct infusion of the CB1R antagonist SR141716 and the MOR antagonist naloxone into the nucleus accumbens core (NAcC). Searching for synaptic correlates of these effects in adolescent NAcC excitatory synapses, we observed that CB1R antagonism blocked the effect of the MOR agonist DAMGO and, conversely, that naloxone reduced the effect of a cannabinoid agonist. These results were recapitulated in mice, and completely abolished in CB1R and MOR knockout mice, suggesting that the functional interaction between CB1R and MOR in the NAcC in the modulation of mediates social behavior is widespread in rodents. The data shed new light on the mechanism by which endocannabinoid lipids and opioid peptides interact to orchestrate rodent socioemotional behaviors.